2011
DOI: 10.1039/c1cc12792f
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient silver niobium alumina catalyst for the selective catalytic reduction of NO by n-decane

Abstract: AgNb/Al(2)O(3) prepared by a nonhydrolytic sol-gel process is a highly efficient catalyst for NO(x) removal through selective catalytic reduction by hydrocarbons (HC-SCR). This result shows that the HC-SCR process remains a challenging method for lean engine DeNO(x).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…NHSG routes have led to promising results in both cases. 93,96,120 To the best of our knowledge, the first example of mixed oxide catalysts prepared by NHSG routes was reported in 2000 by Barbieri and coworkers, 102 who prepared Nb-V and Nb-V-Si catalysts for the ODH of propane. Since then, catalysts prepared by non-hydrolytic sol-gel have been used in a wide range of chemical reactions, including mild and total oxidation, photodegradation, alkene metathesis, and selective catalytic reduction of NO x .…”
Section: Oxide and Mixed Oxide Catalystsmentioning
confidence: 99%
“…NHSG routes have led to promising results in both cases. 93,96,120 To the best of our knowledge, the first example of mixed oxide catalysts prepared by NHSG routes was reported in 2000 by Barbieri and coworkers, 102 who prepared Nb-V and Nb-V-Si catalysts for the ODH of propane. Since then, catalysts prepared by non-hydrolytic sol-gel have been used in a wide range of chemical reactions, including mild and total oxidation, photodegradation, alkene metathesis, and selective catalytic reduction of NO x .…”
Section: Oxide and Mixed Oxide Catalystsmentioning
confidence: 99%
“…1). [34][35][36][37][38][39] The non-ordered porosity is not a disadvantage for most catalytic applications, while the good thermal and hydrolytic stability of NHSG mixed oxide catalysts facilitates their reusability.…”
Section: Tert-butyl Alcohol Routementioning
confidence: 99%
“…The inuence of calcination on the surface composition of the mixed oxides has been studied in detail. [37][38][39][40] When the active metal oxide component has a low Tammann temperature (e.g. VO x , MoO x , ReO x , WO x , AgO x ), appropriate thermal treatments can lead to the migration of active species toward the surface, resulting in an increase of their surface concentration.…”
Section: Tert-butyl Alcohol Routementioning
confidence: 99%
“…The past several years have witnessed a growth in research in NO x reduction by fuel-component hydrocarbons over Ag/Al 2 O 3 , while the light-off temperature for NO x reduction is still too high to be used for commercial application in diesel vehicles, even though it has been reported that low temperature activity can be promoted by the addition of H 2 . 24,[32][33][34][35][36][37][38][39][40] More importantly, aromatic hydrocarbons, typically present in diesel fuel, exhibit low activity for NO x reduction even in the presence of H 2 . 41 Indeed, when using diesel fuel (ultra-low sulfur diesel, US06) as the reductant, 34 Ag/Al 2 O 3 showed high initial activity for NO x reduction in the presence of 3200 ppm H 2 , while its activity gradually decayed with time, reaching a final conversion level similar to that observed in the absence of H 2 .…”
Section: Introductionmentioning
confidence: 99%